KEGIATAN ANAK-ANAK DOWN SYNDROME SEKOLAH LUAR BIASA SINGARAJA DIMASA PANDEMI DALAM FOTOGRAFI DOKUMENTER - Mahendra, Kadek Yoga Riska; Saryana, I Made; Adityasmara, Farhan (Retina Jurnal Fotografi, 2021)
Down syndrome is a genetic disorder that causes sufferers to have a low level of intelligence and experience a distinctive abnormality on the sufferer's face, the WHO data estimates that 3000 to 5000 babies are born with this condition each year, until now in Indonesia concern for children with Down syndrome is still relatively minimal, especially in Bali, due to lack of knowledge about children with special needs with Down syndrome, so many people still isolate children with Down syndrome. The purpose of the creator of using Down syndrome as an object of research is to change the stigma of people who consider Down syndrome to be small and to visualize "Singaraja Special School Down Syndrome Children's Activities in Documentary Photography" so that they get several benefits, namely for creators, they can apply the knowledge gained in lectures. , for Institutions can provide references, and add insight to each individual, for the community can provide information about the activities of children with Down syndrome. In the process of creating a photographic work, the creator uses several methods, including the observation method, literature study, and the interview method, after carrying out the method used as material for the creation of a photographic work, the creator uses EDFAT theory and aesthetics, after using several methods and theories in the creation process, the creator gets a conclusion and the results of 15 documentary photos, regarding the activities of children with Down syndrome Singaraja SLB School, among others, folding clothes, children's learning activities, playing activities and other activities. Keywords: Down Syndrome Children Activities, Singaraja Special School, Documentary Photography